Numerical simulation of in-depth profile control for dispersed particle gel in heterogeneous reservoirs - Sun, Gang; Li, Peichao; Du, Dongyuan; Song, Ting; Lu, Detang (Frontiers in Energy Research, 2023)
Introduction: As a new agent of enhancing oil recovery, the dispersed particle gel (DPG) has been gradually used for in-depth profile control in mature oilfields. Many researchers investigated the preparation, profile control mechanism and application of DPG based on a series of laboratory experiments. However, few numerical studies have been carried out on profile control mechanism of DPG. Methods: This paper proposes a novel mathematical model to proceed numerical simulation of profile control for DPG, considering DPG particles adsorption and weak shear thinning effects. The numerical codes are verified by the UTCHEM simulator. Results and discussion: The effects of the DPG viscosity, the DPG concentration, the water saturation of high permeable regions and the permeability ratio between high and low permeable regions on decreasing the water-cut of producing well are studied. Simultaneously, this paper also investigates the influence of different mobility ratios between high and low permeable regions on water shutoff of DPG. The numerical simulation results show that the effects of DPG profile control become better as the DPG solution viscosity, the suspension concentration and the permeability ratio increase. But the increased water saturation of high permeable regions is not helpful to improve oil recovery. Water plugging effect of DPG becomes worse with increasing mobility ratio between different regions. According to comparison results between DPG profile control and polymer flooding, it is found that DPG profile control is more suitable for heterogeneous reservoirs. These findings are of benefit to guide the efficient field application of DPG profile control in heterogeneous reservoirs.